Assessment of artificial and natural sweeteners present in packaged non-alcoholic beverages (NABs) sold on the Singapore market - Rebecca Tan; Sharon Chew; Xenia Cleanthous; Kimberley Anastasiou; Paige G. Brooker; Theresa Pham; Benjamin P. C. Smith (BMC, 2021)
Abstract Background New Nutri-Grade labelling, aimed at reducing Singaporeans' sugar consumption will be implemented for all pre-packaged non-alcoholic beverages (NABs) sold in retail outlets from end 2021 onwards. It is expected such labelling will have a major impact on sugar content of beverages, as well as the replacement of sugar with non-caloric alternatives. Methods This study used product label data obtained from in-store surveys to investigate sugar and sweetener composition of NABs present on the Singapore market. Using this data we calculated products prospective Nutri-Grade classification in order to compare the current market composition with relation to sugar and/or sweetener use. Results Over half of the NABs on market were sweetened with sugar (59%) and were associated with less healthy Nutri-Grades of 'C' and 'D'. The use of natural sweeteners; Stevia and Monk fruit, remains low (6%). Conclusion With continuous efforts by the government in promoting public health nutrition, it is expected that there will be a greater usage of sugar substitutes among NABs in response to the upcoming implementation of Nutri-Grade and ever-fluctuating consumers' demands. The data collected in this study provide a point estimate (July-September 2020) on market composition and use of both sugar and artificial sweeteners in beverages prior to integration of the mandatory labelling requirements.